From technological teaching training to practices of letters in a school of the public network - Paiva, Francisco Jeimes de Oliveira (Faculdade de Filosofia e Ciências, 2018)
In this study, which was the results of the research project: The Use of Digital Media by Portuguese Language Teachers in the Pact for the Strengthening of Secondary Education (PNEM). We now present some reflections on (multi) of the actions and / or activities, resulting from the line of research: Teaching and Languages, of the Interdisciplinary Master's Program in History and Letters (MIHL), of the State University of Ceará. We opted, for methodological reasons, for the observation and analysis of discursive and interactional practices mediated by TDICs in the development of multiple literacy research with a group of high school teachers from a state public school, E.E.M. Egídia Cavalcante Chagas. In this educational context, we discuss how such (multi) literacy projects can be constituted in strategies of teaching practice that allow to increase the linguistic, discursive and technological knowledge regarding the reading and writing of multimodal textual / discursive genres in virtual learning environments, especially in classes and practices in the computer lab (LEI). We conclude that teachers often know very little about what students know about digital technologies in the classroom and about the use of multimodal and multisemiotic texts in the various contexts of language construction in the age of the digital technologies of communication and information (TDICs), in the current technological and globalized society. Submissão: 2018-07-23 Aceito: 2018-08-26